The FM100-Hue Test Can Detect Poor Color Vision Undetected by Color Vision Screening. - Ng, Jason S. (Optometry & Visual Performance, 2022)
Background: The Farnsworth-Munsell 100-hue test (FM100-hue) is a color-arrangement test wherein a patient must arrange 85 caps into color order. It is a well-known and widely accepted test, but it is not often used in primary eye care practice because it takes a fairly long time (about 10 minutes) to administer. However, this case report will show the usefulness of the test where other tests of color vision were not able to give a clear picture of a patient's color vision issue. Case Report: A 17-year-old Caucasian female presented with a complaint of having trouble distinguishing different shades of similar colors. The patient had a comprehensive eye exam a week prior to this visit, which did not reveal any significant findings. No family history of color vision deficiency was reported. She passed all color vision screening book tests. Additional tests, including the Farnsworth D15, were passed, but with some anomalies. The FM100-hue test was definitively failed and showed a severe (total error score = 372), non-specific color vision issue with errors in every part of the color circle. The patient was diagnosed as likely having genetically normal color vision, but with very poor hue discrimination. Conclusion: The case shows that the FM100-hue test can identify non-specific color vision issues, even when other color vision tests cannot, and the test has utility in clinical practice.